2001
DOI: 10.1080/07391102.2001.10506738
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Protein-Protein Recognition: Whether the Surface Placed Charged Residues determine the Recognition Process?

Abstract: We studied the structure and composition of contact areas in 812 different kind dimeric protein-protein complexes from Brookhaven data base (PDB ) in order to reveal their pecularities with regard to protein-protein recognition. We have found, that the large portion of complexes (approximately 70%) have oppositely charged residues in the contact areas (interfaces) on the subunits surfaces, which form electrostatic contacts - R:E, R:D, K:E, K:D, H:E, H:D. These results are consistent with the current view that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…We preferentially chose residues conserved exclusively in MLH1 proteins, since PMS2 contributed only weakly to the interaction of MutLα with MutSα (31). We furthermore preferred surface placed, charged residues, since most protein interactions include electrostatic interactions (66). We selected 14 residues from the top edge of the extensive β-sheet that backs the MLH1 ATPase (Table 1; Figure 2B and E).…”
Section: Resultsmentioning
confidence: 99%
“…We preferentially chose residues conserved exclusively in MLH1 proteins, since PMS2 contributed only weakly to the interaction of MutLα with MutSα (31). We furthermore preferred surface placed, charged residues, since most protein interactions include electrostatic interactions (66). We selected 14 residues from the top edge of the extensive β-sheet that backs the MLH1 ATPase (Table 1; Figure 2B and E).…”
Section: Resultsmentioning
confidence: 99%
“…Electrostatic interactions have been shown to be important for long distance preorientation of interacting proteins11 and for the stabilization of complexes. In our results, they represent 8% of the contacts in DNA complexes and 7% in RNA complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Ionic interactions between positively charged amino acids and phosphate oxygen are important for stabilizing complexes7, 10 and could be involved in the long‐distance preorientation of peptidic chains 11. In addition, some DNA‐binding proteins bend nucleotide chains, modifying the mechanism of DNA recognition by amino acids 12, 13.…”
Section: Introductionmentioning
confidence: 99%
“…The charge density varies from 0 to 12 charged groups per interface surface . The distribution of the opposite charges in the interfaces of the contacting area showed that salt bridges across them are highly favourable (Drozdov-Tikhomirov et al, 2001;Xu et al, 1997a,b). The desolvation cost of the charged groups in salt-links is lower, since they have favourable interactions with other charges and hydrophilic residues surrounding them (Xu et al, 1997a).…”
Section: Forces Involved In Protein-protein Interactionsmentioning
confidence: 99%